2021
DOI: 10.3389/fphar.2021.731741
|View full text |Cite
|
Sign up to set email alerts
|

Immune Effect of Active Components of Traditional Chinese Medicine on Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancers are heterogeneous, poorly prognostic, and metastatic malignancies that result in a high risk of death for patients. Targeted therapy for triple-negative breast cancer has been extremely challenging due to the lack of expression of estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2. Clinical treatment regimens for triple-negative breast cancer are often based on paclitaxel and platinum drugs, but drug resistance and side effects from the drugs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…By constructing and analyzing molecular networks that underlie breast cancer, researchers can identify critical signaling pathways and potential drug targets that are involved in the development and progression of the disease. Recently, Zhao et al (2021 ) used network-pharmacology-based approaches to identify a potential drug target for triple-negative breast cancer (TNBC), a subtype of breast cancer that is particularly aggressive and difficult to treat. The researchers identified a protein called ITGA5 that plays a critical role in the growth and spread of TNBC cells.…”
Section: Discussionmentioning
confidence: 99%
“…By constructing and analyzing molecular networks that underlie breast cancer, researchers can identify critical signaling pathways and potential drug targets that are involved in the development and progression of the disease. Recently, Zhao et al (2021 ) used network-pharmacology-based approaches to identify a potential drug target for triple-negative breast cancer (TNBC), a subtype of breast cancer that is particularly aggressive and difficult to treat. The researchers identified a protein called ITGA5 that plays a critical role in the growth and spread of TNBC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has indicated that active ingredients in Chinese herbal medicines play a role in inhibiting mechanisms involved in the development of cancer, with stimulating mechanisms associated with disease prevention ( Lam et al, 2022 ). These compounds have been shown to exert anticancer ( Zhao et al, 2021 ), anti-inflammatory ( Tao et al, 2022 ), and anti-oxidant effects ( Gu et al, 2022 ), and may provide new treatment options for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Compounding the challenge, TNBC’s aggressive nature results in a higher risk of distant metastasis, leading to a more dire prognosis compared to other breast cancer subtypes ( Saranya et al, 2020 ; Yang et al, 2021 ). In the clinical realm, the primary therapeutic interventions for advanced TNBC remain anthracycline chemotherapy drugs ( Coates et al, 2015 ; Yu et al, 2020 ; Zhao et al, 2021 ). While these can extend patient survival, their pronounced toxic effects often prove intolerable for many patients ( Goto et al, 2018 ).…”
Section: Heterogeneity and Unique Characteristics Of Wnt/β-catenin Ac...mentioning
confidence: 99%